Pengaruh Literasi Numerasi Terhadap Kemampuan Komunikasi Matematik Siswa Melalui Pendekatan Saintifik Kelas V SD Negeri 0507 Latong - Era Mutiah; Nurhalimah Harahap; Rahmi Hartaty Lubis (Lembaga Intelektual Muda (LIM) Maluku, 2023)
Numeracy literacy is the ability to solve mathematical problems using various types of numbers and symbols practically. Students of SD Negeri 0507 Latong have problems understanding the story problems in the numeracy literacy assessment section, so they need a solution. This study aims to determine the effect of numeracy literacy on students' mathematical communication skills through a scientific approach grade V SD Negeri 0507 Latong. The subjects in this study were class V as many as 37 students with a simple random sampling technique. Data collected using test instruments are then processed with descriptive statistical data analysis techniques and inferential statistical analysis tests. The results of the descriptive analysis showed that the results of the values were normally distributed with the acquisition of the average value of the variable (X) which was 82.97 which was in the medium category and the acquisition of the average value of the variable (Y) 88.11 which was in the medium category. The results of inferential analysis on testing significant data using SPSS found that there was an influence of numeracy literacy on the mathematical communication skills of Class V students of SD Negeri 0507 Latong, Lubuk Barumun District, Padang Lawas Regency